COMPORTAMIENTO DE CENTRIS MIXTA TAMARUGALIS (HYMENOPTERA: ANTHOPHORIDAE), III PARTE: DEPREDACIÓN POR LAGARTOS (IGUANIDAE - Toro, H.; Elórtegui, S.; Chiappa, E. (Acta Entomológica Chilena, 2022)
The result of the predatory activity of Microlophus theresioides acting upon Centris mixta is presented in this paper. The study was carried out in a nesting site of the bee, found in the desert of northern Chile. We examined the feces content of M. theresioides to perform this research, most of the feces contení included remainders of C. mixta (73.18% in October and 12.7% in December), of which 72.5% were males in samples taken in October, while the number of females increased to 57.14% in December. Other groups found in the feces were Mutillidae and Bombyliidae.